An asymmetric Suzuki-Miyaura approach to prostaglandins: Synthesis of Tafluprost - Kučera, R; Goetzke, FW; Fletcher, SP (American Chemical Society, 2020)
We report the catalytic asymmetric synthesis of Tafluprost (1), a prostaglandin analogue. This synthesis demonstrates a new approach to prostaglandins involving symmetrization and desymmetrization of a racemic precursor to control the absolute and relative stereochemistry of the cyclopentyl core. Key steps include a diastereo- and enantioselective Rh-catalyzed Suzuki–Miyaura reaction of a racemic bicyclic allyl chloride and an alkenyl boronic acid and a regio- and diastereoselective Pd-catalyzed Tsuji–Trost reaction with an enolate surrogate.